Pengaruh Motivasi dan Kompensasi Terhadap Kinerja Karyawan - Anas Nuruzzaman; Layla Chilyatul Baroroh; Rizki Mia Audina (Jurnal Syntax Transformation, 2021)
Motivation and compensation as the main factors for assessing the work results (performance) of employees in the company. Because in addition to moral support, employees also have the desire to meet their needs through compensation obtained from the company. This research aims to obtain information on the "Effect of Motivation and Compensation on Employee Performance". This study uses library research methods or review literature by comparing several national journals that have been published before. The results of this study revealed that motivation and compensation have an influence on employee performance both partially and simultaneously.